Re: A couple of Questions

4(x-1)-3(2x+1)=3(x+4)

(4x-4)-(6x-3)=3x+12

4x-4-6x-3=3x+12

4x-6x-4-3=3x+12

-2x-7=3x+12

-7-12=3x-2x

-19=x

Re: A couple of Questions

Quote:

Originally Posted by

**flor** 4(x-1)-3(2x+1)=3(x+4)

(4x - 4) - (6x **+** 3) = 3x +12

-Dan

Re: A couple of Questions

Quote:

Originally Posted by

**bahamamath** Now here's a Simultaneous Equation And Just a quick question ( when using the elimination method , which i use ) how can you tell when to add or subtract?

2x - 3y = 2

3x - 2y = -(7)

What you want to be able to do is to reduce the system to one variable. So let's try to get rid of the variable x. To do this we need to have the same coefficient for x in both equations. In this case, if we multiply the top equation by 3 and the bottom equation by 2 we get

6x - 9y = 6

6x - 4y = -14

If you subtract these two, the x terms disappear.

-Dan